2013
DOI: 10.3892/etm.2013.1119
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of insulin secretion by large-dose oral arginine administration in healthy adults

Abstract: The effects of large-dose oral arginine administration on the secretion of insulin by islet β-cells in healthy adults were determined. Eight non-obese healthy volunteers with normal glucose tolerance participated randomly in tests with four stages (with an interval of at least 3 days): the 300 ml purified water stage (PWS), the 75 g glucose stage (GSS), the 30 g arginine stage (ARS) and the 75 g glucose with 30 g arginine stage (GAS). Venous blood samples were collected to detect the concentrations of glucose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Inducing enteric neuropathy in control mice using cisplatin (Vera et al, 2011) could mimic GLP-1 resistance, further showing the importance of a functional ENS on the control of GLP-1 action. Our conclusions are comforted by few data from the literature, which showed that in humans the NO-donor L-arginine improves meal-induced insulin secretion when administered orally in healthy T2D patients and diabetic mice (Ozbek et al, 2009;Tang et al, 2013). Therefore, a novel therapeutic strategy for the treatment of T2D could emerge and benefit patients notably when GLP-1-based therapies are failing at inclusion or overtime during the treatment.…”
Section: Discussionmentioning
confidence: 74%
“…Inducing enteric neuropathy in control mice using cisplatin (Vera et al, 2011) could mimic GLP-1 resistance, further showing the importance of a functional ENS on the control of GLP-1 action. Our conclusions are comforted by few data from the literature, which showed that in humans the NO-donor L-arginine improves meal-induced insulin secretion when administered orally in healthy T2D patients and diabetic mice (Ozbek et al, 2009;Tang et al, 2013). Therefore, a novel therapeutic strategy for the treatment of T2D could emerge and benefit patients notably when GLP-1-based therapies are failing at inclusion or overtime during the treatment.…”
Section: Discussionmentioning
confidence: 74%
“…The time series data and the calculated kinetic parameters are visualized in Supplemental Figure S4 . The effects of oral arginine ingestion have been investigated in healthy individuals only [ 26 , 27 ] (Supplemental Figure S4A ). One out of the two studies [ 27 ], with the largest oral arginine dose, showed increased insulin concentrations (iAUC, 1.41 µU/mL/min) compared to water intake (iAUC, 0.06 µU/mL/min), with no significant effect on glucose concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the lower insulin peak, the insulin concentrations remained elevated for a longer time after co-ingestion of arginine+glucose. Tang et al [ 27 ] showed a non-significant increase in insulin concentrations when glucose was co-ingested with arginine (iAUC, 28.62 µU/mL/min) compared to glucose ingestion alone (iAUC, 19.05 µU/mL/min). Glucose concentrations were unchanged.…”
Section: Resultsmentioning
confidence: 99%